Bx must be the sum of the numbers in the bracket and c must be the product. So we need to choose 2 numbers that multiply to make 3 and add to make -4.
A negative x negative = positive so
-3*-1=3
-3-1=-4
Therefore:
(x-3)(x-1)
Answer:
19. 11
21. 119
Step-by-step explanation:
19.
(-5)² - [4(-3 ∙ 2 + 4)² + 3] + 5 =
= (-5)² - [4(-6 + 4)² + 3] + 5
= (-5)² - [4(-2)² + 3] + 5
= (-5)² - [4(4) + 3] + 5
= (-5)² - [16 + 3] + 5
= 25 - 19 + 5
= 6 + 5
= 11
21.
5 - 8[6 - (3 ∙ 2 - 8 + 2|4 ÷ -2 + (-3)| - 4) - 7 · 2] - 3² · (-2) =
= 5 - 8[6 - (3 ∙ 2 - 8 + 2|-2 + (-3)| - 4) - 7 · 2] - 3² · (-2)
= 5 - 8[6 - (3 ∙ 2 - 8 + 2|-5| - 4) - 7 · 2] - 3² · (-2)
= 5 - 8[6 - (3 ∙ 2 - 8 + 2(5) - 4) - 7 · 2] - 3² · (-2)
= 5 - 8[6 - (6 - 8 + 10 - 4) - 7 · 2] - 3² · (-2)
= 5 - 8[6 - (-2 + 10 - 4) - 7 · 2] - 3² · (-2)
= 5 - 8[6 - (8 - 4) - 7 · 2] - 3² · (-2)
= 5 - 8[6 - 4 - 7 · 2] - 3² · (-2)
= 5 - 8[6 - 4 - 14] - 3² · (-2)
= 5 - 8[2 - 14] - 3² · (-2)
= 5 - 8[-12] - 3² · (-2)
= 5 - (-96) - 9 · (-2)
= 5 + 96 + 18
= 101 + 18
= 119
Answer:
No they are equivalent
Step-by-step explanation:
3/7 =21/35
3/5=21/35
She is going to need 84 cups of blueberries. 3.5*24= 84 i believe :)
Answer:
C 
Step-by-step explanation:
Consider the series

The nth term of series is 
The bottom index tells you that n starts changing from 3, so

Thus, the sum of all terms is
